1997
DOI: 10.1046/j.1365-2435.1997.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Host selection by virgin and inseminated females of the parasitic wasp, Dinarmus basalis (Pteromalidae, Hymenoptera)

Abstract: Summary 1.Fitness is related to reproduction and survival. There apparently exists a negative correlation between the numbers of male and female offspring. There also exists a trade-off between survival and reproduction. This paper investigates optimal decisions with the reproduction and survival trade-off in host selection by wasps. 2. Whereas inseminated female wasps could manipulate the sex of their offspring, virgin females produced only male offspring. I surveyed behavioural differences and the consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…There are recent reports that foraging strategies of unmated females are different from those of mated females in several parasitoid species (Antolin, 1989; Michaud, 1994; Michaud & Mackauer, 1995; Guertin et al ., 1996; Nishimura, 1997; King et al ., 2000; Mayhew & Heitmans, 2000; King, 2002). Female fitness is considered to be more sensitive to body size than male fitness, so mated females of E. fairchildii may commit infanticide more often.…”
Section: Discussionmentioning
confidence: 99%
“…There are recent reports that foraging strategies of unmated females are different from those of mated females in several parasitoid species (Antolin, 1989; Michaud, 1994; Michaud & Mackauer, 1995; Guertin et al ., 1996; Nishimura, 1997; King et al ., 2000; Mayhew & Heitmans, 2000; King, 2002). Female fitness is considered to be more sensitive to body size than male fitness, so mated females of E. fairchildii may commit infanticide more often.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of all 26 wild bean populations and two commercial Mexican bean cultivars (“Pinto”, “San Lanzano”) were used for performance experiments with A. obtectus and the ectoparasitoid Dinarmus basalis , a solitary idiobiont ectoparasitoid on larvae and pupae of several species of grain and bean weevils [44]. Females of D. basalis are synovigenic, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…When many Callosobruchus chinensis bruchids occur within an azuki bean, the bean is moistened and its tegument becomes softened. Virgin Dinarmus basalis females reduce the costs of oviposition, thereby expanding their lifespan, by laying eggs in these aggregated hosts (Nishimura, 1997). In the present system, where there are no physical barriers to oviposition, host-related differences in handling time could come about Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In these cases, it has been suggested that female parasitoids may not select hosts based on size alone but may use other qualitative criteria, which remain largely unknown. Virgin Dinarmus basalis females reduce the costs of oviposition, thereby expanding their lifespan, by laying eggs in these aggregated hosts (Nishimura, 1997). The high rejection levels of apparently suitable hosts has been observed previously in this (de Jong & van Alphen, 1989;Rivero-Lynch, 1994) and another related (Nell & van Lenteren, 1982;Cade Âe & van Alphen, 1997) koinobiont species and has raised the prospect that host selection behaviour may be based on female assessment of future potential of hosts as a resource for their offspring rather than on current host quality.…”
Section: Discussionmentioning
confidence: 99%